Semantic role universals and argument linking : theoretical, typological, and psycholinguistic perspectives - Bornkessel-Schlesewsky, Ina, 1979- (Trends in linguistics. Studies and monographs, 2006)
Language and the ability to use and acquire language are the most important characteristic of humankind. Linguistics aims at a systematic and scientific study of the wealth of properties of human languages, from different theoretical perspectives, and thus is of central significance for understanding what makes us human. TRENDS IN LINGUISTICS aims at providing a comprehensive forum for publications in Linguistics covering the entire range of language, including its variation and variability in space and time, its acquisition, theories on the nature of human language in general, and description.